Conversion of Human Fibroblasts Into Monocyte‐Like Progenitor Cells. (November 2014) - Pulecio, Julian; Nivet, Emmanuel; Sancho‐Martinez, Ignacio; Vitaloni, Marianna; Guenechea, Guillermo; Xia, Yun; Kurian, Leo; Dubova, Ilir; Bueren, Juan; Laricchia‐Robbio, Leopoldo; Belmonte, Juan Carlos Izpisua
Abstract Reprogramming technologies have emerged as a promising approach for future regenerative medicine. Here, we report on the establishment of a novel methodology allowing for the conversion of human fibroblasts into hematopoietic progenitor‐like cells with macrophage differentiation potential. SOX2 overexpression in human fibroblasts, a gene found to be upregulated during hematopoietic reconstitution in mice, induced the rapid appearance of CD34+ cells with a concomitant upregulation of mesoderm‐related markers. Profiling of cord blood hematopoietic progenitor cell populations identified miR‐125b as a factor facilitating commitment of SOX2‐generated CD34+ cells to immature hematopoietic‐like progenitor cells with grafting potential. Further differentiation toward the monocytic lineage resulted in the appearance of CD14+ cells with functional phagocytic capacity. In vivo transplantation of SOX2/miR‐125b‐generated CD34+ cells facilitated the maturation of the engrafted cells toward CD45+ cells and ultimately the monocytic/macrophage lineage. Altogether, our results indicate that strategies combining lineage conversion and further lineage specification by in vivo or in vitro approaches could help to circumvent long‐standing obstacles for the reprogramming of human cells into hematopoietic cells with clinical potential. Stem Cells2014;32:2923–2938